Midwifery Care for Newborns with Neonatal Physiological Jaundice at the Age of 6 Days at the Clinic: Asuhan Kebidanan Pada Bayi Baru Lahir dengan Ikterus Fisiologis Neonatorum pada Umur 6 Hari di Klinik - Jati, Melinda Indira; Djauharoh, Djauharoh; Cholifah, Siti (Indonesian Journal of Innovation Studies, 2020)
Decrease in Infant Mortality Rate (IMR) according to the Health Office, 2018 In East Java in 2017 it was still within the national target limit (supas), which reached 23.1 per 1000 live births [1]. The Infant Mortality Rate (IMR) in 2017 is still within the national target limit, which is 5.45 per 1000 live births at the Sidoarjo District Health Office, 2018 [2]. Newborns are prone to complications. Jaundice occurs in term or preterm infants. This midwifery care aims to improve the quality of life of newborns to find out health problems as early as possible in the first week that cause physical changes such as yellow appearance on the baby's head (physiological jaundice). This case study was conducted at BPM Dadang Ratih in the village of Jambangan Sidoarjo starting from January 10, 2020. This care was carried out with a patient approach and documentation of the SOAP method. Midwifery care that has been carried out went well and without any complications. In conclusion, the data obtained from the results of data collection did not find any gaps with the theory.